Impact of Capital Structure on Firm Performance of Financial Companies Listed on the Indonesia Stock Exchange - Irvandi Waraney Ombuh; Chrisna Riane Opod; Patricia Steffina Mawitjere; Mumtaz Ahmed (Economy and Finance Enthusiastic, 2024)
In the current business landscape, effective management of a company's financial strategy is paramount for sustainable growth, with a particular emphasis on optimizing the capital structure to fulfill the funding requirements of day-to-day operations. This research investigates how the capital structure influences the financial performance of non-bank financial institutions listed on the Indonesia Stock Exchange in the year 2022. The study focuses on two key dependent variables: the return on assets ratio and the return on equity ratio. The independent variables, represented by the capital structure, encompass the debt-to-assets ratio and the debt-to-equity ratio. The results obtained through regression analysis of the data unveil a significant negative impact of the capital structure on financial performance, particularly affecting the return on equity. These findings underscore the importance of non-bank financial institutions exercising caution when managing capital resources secured through debt financing. Excessive reliance on debt within the company's capital structure could potentially elevate financial burdens, ultimately leading to a reduction in overall profitability. Consequently, prudent capital management practices are recommended to maintain financial stability and bolster long-term prosperity.